2016
DOI: 10.1016/j.dental.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Marginal adaptation, fracture load and macroscopic failure mode of adhesively luted PMMA-based CAD/CAM inlays

Abstract: OBJECTIVES To evaluate marginal adaptation, fracture load and failure types of CAD/CAM polymeric inlays. METHODS Standardized prepared human molars (48) were divided into four groups (n=12): (A) PCG (positive control group); adhesively luted glass-ceramic inlays, (B) TRX; CAD/CAM polymeric inlays luted using a self-adhesive resin cement, (C) TAC; CAD/CAM polymeric inlays luted using a conventional resin cement, and (D) NCG (negative control group); direct-filled resin-based composite restorations. All specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 34 publications
4
28
0
Order By: Relevance
“…(77) Besides the lower modulus of elasticity of VITA ENAMIC compared to e.max CAD, the hybrid restoration might not be able to conform to the loss of a proximal wall in large class 2 cavities and sustain occlusal loading that might be established on tooth restoration interface . These results were consistent with previous study that showed no significant difference between glass ceramic and PMMA based ceramic inlay restorations (78) However, the results of inlay group disagreed with Soares et al (65) , who reported a significant difference in fracture loads of ceramic and polymer based inlays with the later having higher values . This inconsistency in findings might be due to using different ceramic compositions and bonding protocols.…”
Section: Discussionsupporting
confidence: 89%
“…(77) Besides the lower modulus of elasticity of VITA ENAMIC compared to e.max CAD, the hybrid restoration might not be able to conform to the loss of a proximal wall in large class 2 cavities and sustain occlusal loading that might be established on tooth restoration interface . These results were consistent with previous study that showed no significant difference between glass ceramic and PMMA based ceramic inlay restorations (78) However, the results of inlay group disagreed with Soares et al (65) , who reported a significant difference in fracture loads of ceramic and polymer based inlays with the later having higher values . This inconsistency in findings might be due to using different ceramic compositions and bonding protocols.…”
Section: Discussionsupporting
confidence: 89%
“…The elastic modulus of PEEK is increased up to 18 GPa by the reinforcement of the material with carbon fibers. When the elastic modulus is similar to the bone tissue (10)(11)(12)(13)(14)(15)(16)(17)(18), it behaves mechanically in the same manner 36,37) . The elastic modulus of ceramics and metals are high, whereas the modulus of PEEK can be adapted by limiting the complications as a stress shield barrier 19) .…”
Section: Discussionmentioning
confidence: 99%
“…The major advantages of these materials are reduced enamel wear in antagonists, lower costs and time exposure compared to glass-ceramics. Additionally, PMMA-based materials have lower discoloration rate and higher fracture load Load-bearing capacity of novel resin-based fixed dental prosthesis materials compared to composite restorations 17) . Moreover; CAD/ CAM-fabricated PMMA restorations from industrially fabricated resin blocks have higher mechanical stability when compared with conventionally fabricated restorations 18) .…”
Section: Introductionmentioning
confidence: 99%
“…PMMA is a millable block that is used for long term single crowns and fixed partial dentures. A recent study compared the mechanical properties and marginal fit of PMMA inlays to glass‐ceramic inlays, both with similar outcomes . Increased interest in PMMA restorations encouraged the development of PMMA blocks with enhanced optical and physical properties, (eg, Telio CAD, Ivoclar Vivadent, Shaan, Liechtenstein and VITA CAD‐Temp MultiColor Blocks, VITA Zahnfabrik, Bad Sackingen, Germany).…”
Section: Subtractive Manufacturingmentioning
confidence: 99%